VD_FINDINFO HC / 2016 / 254 vom 25. Februar 2016 - VD Tribunal cantonal (2016)
BAIL À LOYER, SUBSTITUTION DE PARTIE, LÉGITIMATION ACTIVE ET PASSIVE | 125 let. a CPC (CH), 308 al. 1 let. a CPC (CH), 83 al. 1 CPC (CH)